The Concept of Post-Non-Classic al Methodological Strategy by Professor Olexander Oguy - Olha Chervinska (Pitannâ Lìteraturoznavstva)
The article under discussion is a survey of how a literary concept of a prominent Ukrainian German Studies expert Olexandr Dmytrovych Oguy has been developing on the pages of a scientific journal “Problems of Literary Criticism” from 1993 till 2013. The article traces up the stages of progress of scientist’s methodological strategy concerning the so-called concept of post-non-classicism, beginning with his first article in “The Issues”, where he presented an efficient sample of involving the timeless linguistic universals with the purpose of comparing the typologically similar genre forms. In this way, he managed to prove the authenticity of “The Tale of Igor’s Campaign” in historical-typological comparison with the medieval epic works (Issue 1, 1993). After a 15-year break, O. Oguy’s articles “A Three-Dimensional Poetic Space of ‘Lanzelet’ by Ulrich von Zatzikhoven” (review, 2010), “The Historical-Social Genres in Post-Non-Classical Methodology: the Principles of Classification” (2012), “The Principles of Formation of the Middle Age German Literature: Overcoming the Crisis Stages through New Genres” (2013) were published in the journal. Each of these works contains a distinct conceptual program. The review was not restricted by a mere critical analysis of the work by a German researcher Kai Lorenz. It also highlighted the difference between methodological fundamentals of European and Ukrainian scientific text analyses – “different paradigms of foreign and Ukrainian Medievalist Studies”. This scientific text is a topical “transplantation” of analytic methodology of K. Lorenz into Ukrainian philological practice. It was introduced into scientific circulation as the so-called “trichotomic model” of functional types of the interacting spatial structures. The article “The Historical-Social Genres in Post-Non-Classical Methodology: the Principles of Classification” (Issue 86, 2012) is a vivid example of a profound present-day academic research. It is worth reading for everyone, who deals with literary genres. The scientist made up his mind to tackle the problem of genres due to the ambiguity of the criteria that existed in Post-Soviet Literary Studies. He activated the notion of “synergic approach”, which enabled him to rethink drastically the whole genre system in the Middle Age literature. O. D. Oguy’s last and largest article “The Principles of Formation of the Middle Age German Literature: Overcoming the Crisis Stages through New Genres” appeared in “Problems of Literary Criticism” in 2013 (Issue 88). It impresses the reader with a broad scope application of diachronic principle in a research space, as well as with the methodology of scientific discourse (the so-called “content analysis”, which presupposes the effect of social factors in investigating the cultural phenomena). The comparison of literary artefacts with the events in European history has enabled O. Oguy to determine and classify eight crisis stages (including the prehistory). The latter had been accompanying the formation of the German nation from the early Christian days and the Great Relocation of Peoples till the end of the Middle Ages, as well as had exercised a direct influence on the changes in the literary process.